A general theory of genital homologies for the Hexapoda (Pancrustacea) derived from skeletomuscular correspondences, with emphasis on the Endopterygota. Issue 6 (November 2018) - Boudinot, Brendon E.
Abstract: No consensus exists for the homology and terminology of the male genitalia of the Hexapoda despite over a century of debate. Based on dissections and the literature, genital skeletomusculature was compared across the Hexapoda and contrasted with the Remipedia, the closest pancrustacean outgroup. The pattern of origin and insertion for extrinsic and intrinsic genitalic musculature was found to be consistent among the Ectognatha, Protura, and the Remipedia, allowing for the inference of homologies given recent phylogenomic studies. The penis of the Hexapoda is inferred to be derived from medially-fused primary gonopods (gonopore-bearing limbs), while the genitalia of the Ectognatha are inferred to include both the tenth-segmental penis and the ninth-segmental secondary gonopods, similar to the genitalia of female insects which comprise gonopods of the eighth and ninth segments. A new nomenclatural system for hexapodan genitalic musculature is presented and applied, and a general list of anatomical concepts is provided. Novel and refined homologies are proposed for all hexapodan orders, and a series of groundplans are postulated. Emphasis is placed on the Endopterygota, for which fine-grained transition series are hypothesized given observed skeletomuscular correspondences. Highlights: The penis of the Hexapoda is derived from medially-fused gonopods. Ectognathan genitalia include secondary gonopods from the preceeding segment. Ephemeroptera and Neoptera have intromittent penes, the latter with a novel protractor muscle. New genital skeletomuscular apomorphies and nomenclature are proposed based on all orders. Emphasis is placed on correspondences and inferred transformations of the Endopterygota.